Treatment of breast ptosis with submuscular implants and points of attachment of the breast to the pectoralis muscle: technical considerations and outcome assessment - Antonio Chiquetti; Alfredo Benjamin Duarte da Silva (Revista Brasileira de Cirurgia Plástica, 2018)
Introduction: Mastopexy associated with implant placement is challenging for plastic surgeons. The objective is to describe the placement of a submuscular implant with anatomical detachment in combination with stable fixation of the breast tissue to the pectoralis muscle and analyze the aesthetic results. Method: Twenty-three mastopexy procedures with implants were performed from April 2015 to July 2017 by the same surgeon, and surgical markings were made in the breasts of the patients in a seated position. An incision was made in the inframammary fold, and the breast tissue was elevated to the upper pole in the subfascial plane and attached to the pectoralis major muscle using 9-12 stitches. Subsequently, the inferior margin of the pectoralis major muscle and the transition from the rectus abdominis muscle to the serratus muscle were dissected to expose the muscle. The implant was introduced and mastopexy was completed. Implant size ranged from 255 mL to 355 mL. Photographs of the breasts of 12 patients were evaluated by two plastic surgeons and two non-medical subjects, who considered the aesthetic results, symmetry of the nipple-areola complex, and degree of breast ptosis. The results were scored as unsatisfactory, satisfactory, or good. Results: The surgical technique was reproducible; there was only one case of unilateral hematoma, no implant infections, and only complaints of mild pain. Only one case was scored as satisfactory by one evaluator, whereas the results of the other cases were considered good. Conclusion: The treatment of breast ptosis with the placement of a submuscular implant in combination with fixation of the breast to the pectoralis major muscle is reproducible and yields good aesthetic results.